Current Status/ Role of Biophysical Studies in Integrated Coastal Management Sustainability in Selected Sites in Negros Oriental and Sogod Bay, Leyte, Philippines - De Leon, Roy Olsen D. (Silliman Journal, 2022)
Biophysical studies have become an integral part of the Integrated Coastal Management (ICM) process. Such studies in most cases take a significant portion of the ICM budget costing about 14 per cent of the year 1 budget per kilometer of coastline. Yet, a review of different Coastal Resource Management (CRM) resource profiles and plans, legislation developed in aid of CRM, and augmented by interviews of 30 key informants in selected sites reveals that the biophysical data generated are underutilized. A trace of the flow of information in the 1CM process cycle further reveals that in most cases, the information stops in the planning stage. The low utilization of information can be attributed to problems in accessing the information, lack of perceived need for the information, or lack of technical know how in utilizing the information as well as updating the information.